Target reliability of structures in the context of Bayes’ theorem - Pokorný, Jiří; Suchánek, Vladimír; Vnenk, Petr (University of Pardubice, 2018)
This paper deals with target reliability determination of structures. In the first part, terms risk and reliability are delimited. Further, the difference between the understanding of reliability in civil and machinery engineering is shown. The widely used safety index is a subject of a deeper analysis and its relation to target reliability is presented. The second part of this paper contains a summary of a target reliability estimation, as it is calculated in the present time, and a draft of an alternative approach to the target reliability determination using the Bayes’ theorem.
Keywords: risk; safety; structure; probability; Bayes’ theorem